Pengaruh Inventory Turnover Dan Volume Penjualan Terhadap Laba Bersih - Agus Solikin (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2020)
This study aims to determine whether there is an effect between sales and inventory turnover on net income at UD. Sido Mulyo, which is located in Ds. Sumberjo, Sutojayan District, Blitar Regency. This study uses a quantitative approach with secondary data collection. The analysis technique used is multiple linear regression with the help of the SPSS program. The results showed that inventory turnover and sales both had a significant effect on net income. These results indicate that the net income received by the company can be predicted through an increase in inventory turnover and sales in accordance with the theory.